Species composition and distribution of the dipterans (Insecta: Diptera) in Bulgaria - Hubenov, Zdravko (Advanced Books, 2021)
The aim of this work is to present the fauna, distribution according to the vegetation belts and zoogeography of the order Diptera in Bulgaria.